Red Maca (Lepidium meyenii) did not affect cell viability despite increased androgen receptor and prostate‐specific antigen gene expression in the human prostate cancer cell line LNCaP. (29th September 2016) - Díaz, P.; Cardenas, H.; Orihuela, P. A.
Summary: We examined whether aqueous extract of Lepidium meyenii (red Maca) could inhibit growth, potentiate apoptotic activity of two anticancer drugs Taxol and 2‐methoxyestradiol (2ME) or change mRNA expression for the androgen target genes, androgen receptor ( Ar ) and prostate‐specific antigen ( Psa ) in the human prostate cancer cell line LNCaP. Red Maca aqueous extract at 0, 10, 20, 40 or 80 μg/ml was added to LNCaP cells, and viability was evaluated by the MTS assay at 24 or 48 hr after treatment. Furthermore, LNCaP cells were treated with 80 μg/ml of red Maca plus Taxol or 2ME 5 μM and viability was assessed 48 hr later. Finally, LNCaP cells were treated with red Maca 0, 20, 40 or 80 μg/ml, and 12 hr later, mRNA level for Ar or Psa was assessed by real‐time PCR. Treatment with red Maca did not affect viability of LNCaP cells. Apoptotic activity induced by Taxol and 2ME in LNCaP cells was not altered with red Maca treatment. Relative expression of the mRNA for Ar and Psa increased with red Maca 20 and 40 μg/ml, but not at 80 μg/ml. We conclude that red Maca aqueous extract does not have toxic effects, but stimulates androgen signalling in LNCaP cells.